2022
DOI: 10.1002/bit.28113
|View full text |Cite
|
Sign up to set email alerts
|

Coevolutionary analysis reveals a distal amino acid residue pair affecting the catalytic activity of GH5 processive endoglucanase from Bacillus subtilis BS‐5

Abstract: EG5C‐1, processive endoglucanase from Bacillus subtilis, is a typical bifunctional cellulase with endoglucanase and exoglucanase activities. The engineering of processive endoglucanase focuses on the catalytic pocket or carbohydrate‐binding module tailoring based on sequence/structure information. Herein, a computational strategy was applied to identify the desired mutants in the enzyme molecule by evolutionary‐coupling analysis; subsequently, four residue pairs were selected as evolutionary mutational hotspot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 47 publications
(99 reference statements)
2
21
0
Order By: Relevance
“…Notably, mutants TJN and TJA exhibited pronounced fluctuation within region 195–210, where the extra sequence is added. This indicated that the loop alteration increases the flexibility of the enzyme, potentially hindering the entry of the substrate during the catalytic process . These observations align with alterations in the catalytic activity.…”
Section: Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Notably, mutants TJN and TJA exhibited pronounced fluctuation within region 195–210, where the extra sequence is added. This indicated that the loop alteration increases the flexibility of the enzyme, potentially hindering the entry of the substrate during the catalytic process . These observations align with alterations in the catalytic activity.…”
Section: Results and Discussionsupporting
confidence: 59%
“…This indicated that the loop alteration increases the flexibility of the enzyme, potentially hindering the entry of the substrate during the catalytic process. 46 These observations align with alterations in the catalytic activity.…”
Section: ■ Results and Discussionsupporting
confidence: 56%
“…This prospect has therefore engendered significant attention. 12,13 Compared to CBHs, much less is known about the structure and function of processive EGs. They belong almost exclusively to the glycoside hydrolase family 9 (GH9) of enzymes associated with the bacterial cellulolytic system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…HotSpot Wizard server can be used for mutation site identification and library design [ 17 ], which has predicted hotspots of mutations for increasing enzyme activity [ 18 , 19 , 20 ]. EVcoupling web server can provide evolutionary constraints (EC) to infer correlations between amino acids at different sequence positions [ 21 ] and affect enzyme structure and function [ 22 ], which has been proved to be an effective approach to improving catalytic activity [ 23 , 24 ]. However, enzymatic improvement of type II ASNase by rational design combing structural information and bioinformatics tools has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%